A Portrait of the Urban Demographic Profile of an African City—Port Harcourt, Nigeria - Adaku Jane Echendu (Urban Science)
The global population is experiencing a remarkable demographic shift. The population pyramid of African countries looks very different from that of the West, with a youthful population forming the base of the African population, while the population of Western countries has a larger share of an aging population. A broader understanding of the various facets of urban growth in Africa is needed, including the demographic makeup and drivers of growth. However, inadequate attention has been paid to this aspect of urban change in research, even though this knowledge can aid development planning. Demographic concerns like the interconnections between development and population are important issues of national dialogues and debates. Research from Southern Africa has also found a prevalence of female-headed households in urban areas and predicts a rise in this trend. This study thus set out to explore the primary factor behind urban population growth and the extent of prevalence of female-headed households in African cities using Port Harcourt, Nigeria, as a case study. Quantitative research was conducted. The findings revealed that natural increase was largely responsible for urban growth, given the proportion of participants in the age group 18–40 born in the city. This group currently forms the large base of the African urban population. Results also showed that male-headed households were still dominant in Port Harcourt city. This study highlights the need for expansion of similar research in other cities to enable a more holistic understanding of the wider African urban population demographics and dynamics.